Terrorism: Between Islamic Radicalism and Misinterpretation of J i h a d Doctrine - Alfiah Alfiah (JICSA : Journal of Islamic Civilization in Southeast Asian, 2013)
This article discusses the relationship between Islam and terrorism. The West accuses Islam as a religion inspiring the act of terrorism. This accusation stemmed from the fact that there are many terrorist attacks perpetrated by extremist Muslims in the name of Islam. This article argues that there is no single verse in the Holy Qur’an that teaches Muslims to commit the acts of terrorism. The rise of violence in the Muslim world is a result of internal factors other than religion such as unjust social and economic Muslim condition, repressive domestic political regime and the West intervention in Muslim politics. This article also shows that some extremist Muslims misinterpret doctrine of Jihad and uses such doctrine to achieve their political aims.